2022
DOI: 10.1101/2022.01.10.475645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of a transparent soil system to study Bacillus subtilis chemical ecology

Abstract: Bacterial secondary metabolites are structurally diverse molecules that drive microbial interaction by altering growth, cell differentiation, and signaling. Bacillus subtilis, a Gram-positive soil-dwelling bacterium, produces a wealth of secondary metabolites, among them, lipopeptides have been vastly studied by their antimicrobial, antitumor, and surfactant activities. However, the natural functions of secondary metabolites in the lifestyles of the producing organism remain less explored under natural conditi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Nafion was selected due to its commercial availability, documented use for bioimaging, stability during autoclave sterilisation, low refractive index, potential for particle size refinement, and ion exchange capacity for nutrient imbibement [15,34]. Using Nafion surmounted the optical and material complexities and costs of previously published artificial soil scaffolds such as those using cryolite [17,35], FEP [36], silica [37,38], and hydrogels [32,39]. The material properties of Nafion permitted particle size refinement from centimetre to micron-scale particles.…”
Section: Discussionmentioning
confidence: 99%
“…Nafion was selected due to its commercial availability, documented use for bioimaging, stability during autoclave sterilisation, low refractive index, potential for particle size refinement, and ion exchange capacity for nutrient imbibement [15,34]. Using Nafion surmounted the optical and material complexities and costs of previously published artificial soil scaffolds such as those using cryolite [17,35], FEP [36], silica [37,38], and hydrogels [32,39]. The material properties of Nafion permitted particle size refinement from centimetre to micron-scale particles.…”
Section: Discussionmentioning
confidence: 99%
“…Nafion™ was selected due to its commercial availability, documented use for bioimaging, stability during autoclave sterilisation, low refractive index, potential for particle size refinement, and ion exchange capacity for nutrient imbibement (18,34). Using Nafion™ surmounted the optical and material complexities and costs of previously published artificial soil scaffolds, such as those using cryolite (20,35), fluorinated ethylene propylene (36), silica (37,38), and hydrogels (39,40). Moreover, we demonstrated that our platform was compatible with conventional fluorescence microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in single-cell microscopy, transcriptomics and molecule tracking will likely continue to push our understanding of surface-bound microbial communities [21,54,55]. In addition, we believe important challenges lie in developing laboratory settings that most accurately reflect the complex ecologies to which bacteria are exposed in nature [56].…”
Section: Discussionmentioning
confidence: 99%